A Meta-Analysis of the Predictors of On-time High School Graduation in the United States. (June 2023) - Zheng, Yunzheng; Gao, Xingyuan; Shen, Jianping; Johnson, Megan Russell; Y. Krenn, Huilan
On-time high school graduation is an important topic in educational research, policy, and practice. However, no comprehensive meta-analyses had been conducted on this topic. The current meta-analysis reviewed 47 articles published from 1985 to April 2022 and aggregated the effect in four dimensions: student background, family support, school program and support, and school climate, with a focus on school-related practices, policies, and programs. Twelve factors along various dimensions had statistically significant positive or negative effects on on-time graduation. Implications of these findings are discussed.